2008
DOI: 10.1007/s10531-008-9534-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevational patterns of species richness and endemism for some important taxa in the Hengduan Mountains, southwestern China

Abstract: We describe the elevational patterns of species richness and endemism of some important taxa in the Hengduan Mountains, southwest China. Species richness data came from publications, an online database, herbaria and Weld work. Species richness was estimated by rarefaction and interpolation. The Hengduan Mountains region was divided into a southern and northern subregion, and all species were assigned to four groups based on their distributional range within this region. The conditional autoregressive model (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
60
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 33 publications
9
60
0
Order By: Relevance
“…Previous studies conducted in this area had already found that the highest plant richness occurred at mid-elevationsZhang e al., 2009; but seeBhatta et al, 2018). Previous studies conducted in this area had already found that the highest plant richness occurred at mid-elevationsZhang e al., 2009; but seeBhatta et al, 2018).…”
mentioning
confidence: 75%
“…Previous studies conducted in this area had already found that the highest plant richness occurred at mid-elevationsZhang e al., 2009; but seeBhatta et al, 2018). Previous studies conducted in this area had already found that the highest plant richness occurred at mid-elevationsZhang e al., 2009; but seeBhatta et al, 2018).…”
mentioning
confidence: 75%
“…3a). Zhang et al (2008) found that richness patterns of total, endemic and non-endemic plant species were unimodal and peaked at high elevations (3500-4500 m); plant species richness was strongly related to area and weakly correlated with precipitation. Other recent studies in the Hengduan Mountains have documented the species richness patterns for plants, insects, reptiles and mammals (Gong et al, 2005;Fu et al, 2007;Zhang et al, 2008;Li et al, 2009;Wu et al, 2013), which revealed a hump-shaped pattern with maxima occurring at different elevations along the elevational gradient.…”
Section: Comparison Of Species Richness Patterns and Explanatory Factmentioning
confidence: 97%
“…Different elevational richness patterns have been reported from different taxa, e.g. Previous studies focusing on species richness patterns in mammals, reptiles, fish and plants along the elevational gradient in the Hengduan Mountains (China) demonstrated that species richness patterns differ widely among life forms, and the corresponding explanations are also diverse and controversial (Fu et al, 2006(Fu et al, , 2007Wang et al, 2007;Zhang et al, 2008;Li et al, 2009;Wu et al, 2013). Rahbek (1995Rahbek ( , 2005 documented that patterns of species richness along elevational gradients can generally be classified into four forms: monotonically decreasing richness with elevation, low-elevation richness plateaux followed by a decrease with elevation, lowelevation plateaux with mid-elevation richness peaks, and unimodal mid-elevational peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Analogous to species richness-elevation relationships, two main patterns of endemic species richness-elevation relationships have been documented, i.e. increasing [13]–[15] and unimodal [11], [16], [17]. The increase of endemism with elevation has been attributed to the increased isolation of higher elevations.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have mainly been focused on the large mountain massifs of the world [11], [12], [14], [15], [17], [25]–[30] and on tropical islands [31]–[35]. Moreover, the combined effect of island and mountain isolation in the formation of elevational gradient patterns of species richness and endemism of island biota has received little attention.…”
Section: Introductionmentioning
confidence: 99%